(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes the effectiveness of using innovative technologies in the lessons of the native language and reading literacy and their significance for modern science. The article revealed that the use of modern teaching methods leads to high efficiency of the educational process and the advisability of choosing these methods based on the didactic task of each lesson.